Fluctuations of Spleen Cytokine and Blood Lactate, Importance of Cellular Immunity in Host Defense Against Blood Stage Malaria Plasmodium yoelii - Imai, Takashi; Suzue, Kazutomo; Ngo-Thanh, Ha; Ono, Suguri; Orita, Wakako; Suzuki, Haruka; Shimokawa, Chikako; Olia, Alex; Obi, Seiji; Taniguchi, Tomoyo; Ishida, Hidekazu; Van Kaer, Luc; et al. (Frontiers in Immunology, 2019)
Previously we identified that not only CD4+ T cells, but also CD8+ T cells and macrophages, are important for host defense against blood stage malaria infection. Further, we found that Plasmodium yoelii 17XNL (PyNL) parasitizes erythroblasts, the red blood cell (RBC) precursor cells. Parasitized erythroblasts express MHC class I molecules. In the present study, we analyzed spleen cytokine production, and evaluated the involvement of factors downstream of IFN- and cellular immunity against blood stage malaria parasites. Furthermore, we tried to identify the cause of death in malaria infection. At day 16 after PyNL infection, CD8+ T cells produced more IFN- than CD4+ T cells. In CD8+ T cell-depleted mice, IL-10 production in early stage infection was increased over two-fold relative to infected control animals and IL-10+ CD3- cells were increased, whereas IFN- production in the late stage of infection was decreased. Blood lactate concentration was increased in the CD8+ T cell-depleted PyNL-infected group at day 19 (around peak parasitemia) to similar levels as day 7 after infection with a lethal strain of Py. When we injected mice with lactate at day 4 and 6 of PyNL infection, all mice died at day 8 despite demonstrating low parasitemia, suggesting that hyperlactatemia is one of the causes of death in CD8+ T cell-depleted PyNL-infected mice. In cell transfer experiments, donor mice receiving immunized immunoproteasome-related factor Knockout CD8+ T cells were slightly less resistant to infection than donor mice receiving CD8+ T cells derived from immunized WT mice, but all mice were able to develop immunity against PyL infection, thus suggesting that at least the single molecules LMP7, LMP2 and PA28 are not essential for CD8+ T cell induction. The Fas mutant LPR mouse was weaker in resistance to PyNL infection than WT mice, and 20% of the animals died. LPR-derived parasitized erythroid cells exhibited less externalization of phosphatidylserine (PS), and phagocytosis by macrophages was impaired. If the defense mechanisms of CD8+ T cells against malaria can be analyzed in detail and CD8+ T cells can be controlled clinically, selective ablation of malaria parasites and elimination of host pathogenicity may be possible.